RIDDLES OF THE SCREEN / ЗАГАДКИ ЭКРАНОВ - DUKOV E.V. / ДУКОВ Е.В. (Наука телевидения)
The article is devoted to the evolution of the screen in the history of Western European culture. The author argues that technological change contributed to greater reliability of the on-screen image. Stereography, panoramic shooting, color, stereo sound helped to create a «presence effect», made the screen image equivalent to real life. Computer technology reinforced this trend: audio-visual culture has become part of the environment, determining human existence.